MdRDH1, a HSP67B2-like rhodanese homologue plays a positive role in maintaining redox balance in Musca domestica. (March 2019) - Tang, Ting; Sun, Hehe; Li, Yongbao; Chen, Peiru; Liu, Fengsong
Highlights: The first insect rhodanese homologue, MdRDH1 with sulfurtransferase activity was identified in M. domestica . The transcription of MdRDH1 can be enhanced by bacterial infection and oxidative stress. Silencing MdRDH1 caused accumulations of ROS and MAD, and an increased mortality in housefly following bacterial invasion. Overexpressing MdRDH1 improved the viability of E. coli under oxidative stress insulted by PMS. Abstract: Rhodanese homology domains (RHODs) are the structural modules of ubiquitous tertiary that occur in three major evolutionary phyla. Despite the versatile and important physiological functions of RHODs containing proteins, little is known about their invertebrate counterparts. A novel HSP67B2-like single-domain rhodanese homologue, MdRDH 1 from Musca domestica, whose expression can be induced by bacterial infection or oxidative stress. Silencing MdRDH 1 through RNAi causes important accumulations of reactive oxygen species (ROS) and malondialdehyde (MDA), and increases mortality in the larvae treated with bacterial invasion. The E. coli with MdRDH1 and the mutant MdRDH1 C135A are transformed, with significant rhodanese activity of the recombinant protein of MdRDH1 in vitro found, without no detection of enzyme activity of the mutant MdRDH1 C135A, revealing that catalytic Cys135 in the active-site loop is essential in the sulfurtransferase activity of MdRDH1. When oxidative stress is insulted by phenazine methosulfate (PMS), the MdRDH 1 transformed E. coli shows enhanced survival rates compared with those bacteria transformed with MdRDH1 C135A . Our research indicates that MdRDH1 confers oxidative stress tolerance, thus rendering evidence for the idea that rhodanese family genes play a critical role in antioxidant defenses. This paper yields novel insights into the potential antioxidative and immune functions of HSP67B2-like rhodanese homologues in invertebrate.